Temperature-inducible outer membrane protein of Yersinia pseudotuberculosis and Yersinia enterocolitica is associated with the virulence plasmid. - Bölin, I (1982)
A strain of Yersinia pseudotuberculosis which harbors a 63-kilobase plasmid was found to cause a lethal infection in Swiss albino mice. The rate of infection paralleled the ability of the pathogenic organism to attach to a monolayer of HeLa cells. One novel outer membrane protein (protein 1) with a molecular weight of 140,000 was found to be associated with the possession of the 63-kilobase plasmid not at 26 degrees C, and expression was moderately affected by the concentration of calcium in the growth medium. Moreover, it was found that synthesis of protein 1 associated outer membrane protein showing similar properties was also found to be expressed in plasmid-containing strains of Yersinia enterocolitica. The properties of protein 1 indicate that it could be identical to the previously described virulence W antigen.